Virtual technologies concepts, methodologies, tools and applications - Kisielnicki, Jerzy. (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2008)
This book includes the most encompassing research of the concepts and realities involved in the field of virtual communities and technologies. A ground-breaking, multi-volume compendium of 167 chapters from a global pool of more than 350 experts, it presents an in-depth analysis of the technologies and social and economic impacts of virtual environments, comprising such topics as collaborative technologies, resource-based view strategy, structuration theory, synchronous and asynchronous environments, and videoconferencing life-cycle.